The relationship between EFL Saudi university students' vocabulay knowledge and listening comprehension - Kamariah, Yunus; Hamzah Faleh, Migdadi; Amer Ahmed, Daradkeh (2019)
The present study purports to examine the relationship between Saudi University students’ text-based vocabulary knowledge and their listening comprehension in English. It aims at revealing the basic component (Breadth or Depth) of vocabulary knowledge in listening comprehension. Forty preparatory year Saudi University students at Prince Sattam bin Abdulaziz University took three tests: Breadth of vocabulary knowledge test, Depth of vocabulary knowledge test, and Listening comprehension test. Both vocabulary knowledge revealed a strong relationship (Breadth = 0.73, Depth = 0.59) with listening comprehension. The study found that breadth and depth of vocabulary knowledge can explain (0.54) of the variance in listening comprehension. Moreover, the findings suggest breadth of vocabulary knowledge might be the basic component in listening comprehension. In teaching English, the need is to focus explicitly on learners’ breadth of vocabulary knowledge that enables them to achieve successful listening comprehension outcomes.